PENGARUH APLIKASI CANVA TERHADAP KREATIVITAS PEMBELAJARAN IPA - Jefryadi Jefryadi; Ummi Khoriyah (Tarbiyah al-Awlad, 2022)
AbstractCreativity is an ability, potential, talent that every human being has. Creativity is very important in everyday life, because creativity is an ability that is used to create something new or create something old to become new. To bring out or create creativity, Melanie Perkins and her partner, Cliff Obrecht, to be precise, in August 2013 created a lightweight and easy-to-learn software called Fusion Books. Fusion Books is what will become the Canva Application. The Canva app is an online design program that provides a wide range of tools such as creative presentations, posters, brochures, graphics, resumes, flyers, infographics, banners, bookmarks, bulletins and so on.This study aims to answer three questions, namely how to use the Canva Application for class VI students at MI Al-Istiqomah, Nibung District, how is the creativity in science learning for students in class VI at MI Al-Istiqomah, Nibung District, North Musi Rawas Regency, how does the Canva application affect creativity in learning science for students class VI MI Al-Istiqomah, Nibung District, North Musi Rawas Regency. This research is a quantitative research, the methods used to obtain data are questionnaires, interviews, and documentation.From the results of this study it can be seen that there is an influence between the use of the Canva application on the creativity of science learning for class VI MI Al-Istiqomah students, Nibung District, North Musi Rawas Regency, which is in the high category. It is evident from the results of the calculation of the correlation coefficient interpretation analysis, which is equal to 0.91, meaning that between the effect of using the Canva application on the creativity of science learning for class VI MI Al-Istiqomah students, there is a very high or very strong relationship so that the correlation can be accepted.Keywords: Canva Application, Science Learning Creativity